2019
DOI: 10.1371/journal.pone.0218923
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the neurotransmitter systems through the anti-inflammatory and antidepressant-like effects of squalene from Aurantiochytrium sp.

Abstract: Although algae have been the focal point of biofuel research, studies on their biological activities have been limited. In recent years, however, the importance of algae as sources of functional ingredients has been recognized due to their health beneficial effects. In this study, we evaluated the antidepressant-like activities of ethanol extract of Aurantiochytrium sp. (EEA) in the forced swimming test (FST)-induced depression in ICR mice. Imipramine, a commercially available tricyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
2
14
0
1
Order By: Relevance
“…In our previous study, we orally administered 100 mg/kg of EEA for 14 consecutive days to depression model mice to evaluate its antidepressant-like activities (Sasaki et al, 2019a ). Considering this previous study, 50 mg/kg was determined as the concentration for oral administration of EEA and HEEA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we orally administered 100 mg/kg of EEA for 14 consecutive days to depression model mice to evaluate its antidepressant-like activities (Sasaki et al, 2019a ). Considering this previous study, 50 mg/kg was determined as the concentration for oral administration of EEA and HEEA.…”
Section: Methodsmentioning
confidence: 99%
“…(EEA) had anti-inflammatory effects on RAW264.7 cells (Takahashi et al, 2018 ). Moreover, EEA also showed an antidepressant-like effect via anti-inflammation (Sasaki et al, 2019a ). However, the effects of Aurantiochytrium sp.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that HEEA can induce differentiation of NPC into both neurons or glia while EEA keeps them in an undifferentiated state. Recent studies showed EEA and one of its active components, squalene, have neuroprotective effects, protecting stressed neurons from cell death [10]. Several genes related to chemokine signaling pathways are downregulated in EEA-treated mice and may contribute to anti-in ammatory effects [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed EEA and one of its active components, squalene, have neuroprotective effects, protecting stressed neurons from cell death [10]. Several genes related to chemokine signaling pathways are downregulated in EEA-treated mice and may contribute to anti-in ammatory effects [10]. Squalene, which is concentrated in the HEEA layer, is essential in NSCs and NPC cholesterol biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation